Advances in clinical studies of cardiopulmonary resuscitation - Chen, Shou-quan (World J Emerg Med, 2015)
BACKGROUND: The survival rate of patients after cardiac arrest (CA) remains lower since 2010 International Consensus on Cardiopulmonary Resuscitation (CPR) and Emergency Cardiovascular Care (ECC) was published. In clinical trials, the methods and techniques for CPR have been overly described. This article gives an overview of the progress in methods and techniques for CPR in the past years. DATA SOURCES: Original articles about cardiac arrest and CPR from MEDLINE (PubMed) and relevant journals were searched, and most of them were clinical randomized controlled trials (RCTs). RESULTS: Forty-two articles on methods and techniques of CPR were reviewed, including chest compression and conventional CPR, chest compression depth and speed, defibrillation strategies and priority, mechanical and manual chest compression, advanced airway management, impedance threshold device (ITD) and active compression-decompression (ACD) CPR, epinephrine use, and therapeutic hypothermia. The results of studies and related issues described in the international guidelines had been testified. CONCLUSIONS: Although large multicenter studies on CPR are still difficult to carry out, progress has been made in the past 4 years in the methods and techniques of CPR. The results of this review provide evidences for updating the 2015 international guidelines.